1996
DOI: 10.1046/j.1468-2982.1996.1602087.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhalational Anesthetics Inhibit Spreading Depression: Relevance to Migraine

Abstract: Cortical spreading depression (SD) has not been shown in the human neocortex by direct cortical recordings. However, animal studies suggest that cortical injury, such as that occurring during neurosurgical procedures, should result in the initiation of SD. It is possible that inhibition of SD by volatile anesthetic agents may partially explain the failure to observe SD in the human neocortex during surgery. This study examines the effect of the anesthetic agents alpha-chloralose, halothane, nitrous oxide and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…In contrast, Saito et al found a complete suppression of KCl-evoked CSDs in cats under 0.7 MAC halothane when compared to α-chloralose, although both groups received 70% N 2 O, which may have potentiated the CSD suppression by halothane as observed in our study (Saito, et al, 1995). In another study, halothane (1-1.5 MAC) was more effective in suppressing pinprick-induced CSDs compared to isoflurane (1.5 MAC); at this concentration, however, isoflurane still suppressed CSDs compared to α-chloralose (Piper and Lambert, 1996). Using a continuous topical 3M KCl application similar to ours, the frequency of evoked CSDs was suppressed in a concentration-dependent manner by halothane, isoflurane and sevoflurane; the lowest isoflurane concentration that suppressed CSDs was 1 MAC, while CSD frequency under 0.5 MAC isoflurane did not differ from pentobarbital (Kitahara, et al, 2001).…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…In contrast, Saito et al found a complete suppression of KCl-evoked CSDs in cats under 0.7 MAC halothane when compared to α-chloralose, although both groups received 70% N 2 O, which may have potentiated the CSD suppression by halothane as observed in our study (Saito, et al, 1995). In another study, halothane (1-1.5 MAC) was more effective in suppressing pinprick-induced CSDs compared to isoflurane (1.5 MAC); at this concentration, however, isoflurane still suppressed CSDs compared to α-chloralose (Piper and Lambert, 1996). Using a continuous topical 3M KCl application similar to ours, the frequency of evoked CSDs was suppressed in a concentration-dependent manner by halothane, isoflurane and sevoflurane; the lowest isoflurane concentration that suppressed CSDs was 1 MAC, while CSD frequency under 0.5 MAC isoflurane did not differ from pentobarbital (Kitahara, et al, 2001).…”
Section: Discussionsupporting
confidence: 43%
“…General anesthetics modulate CSD susceptibility (Guedes and Barreto, 1992, Kitahara, et al, 2001, Piper and Lambert, 1996, Saito, et al, 1997, Saito, et al, 1995, Sonn and Mayevsky, 2006, Verhaegen, et al, 1992. Interestingly, nitrous oxide (N 2 O), an inhalational anesthetic frequently used as an adjunct with other general anesthetics in experimental models, reportedly shows clinical efficacy in aborting acute migraine (Triner, et al, 1999), whereas normobaric hyperoxia (100% O 2 ) is ineffective (Myers and Myers, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggest that FHM1 mutations facilitate corticostriatal SD propagation. The anesthetic regimen used in our model may explain the complete lack of corticostriatal SD propagation in WT mice (63,64).…”
Section: Figurementioning
confidence: 99%
“…1 Clinically, CSD is postulated to play a role in the pathogenesis of stroke, 2 traumatic cortical injury, 3 cerebral ischemia, 4,5 migraine, 6 and transient global amnesia. 7 CSD can be induced by a variety of stimuli including pinprick or needle stab, 8,9 elevated potassium, 5,10 electrical stimulation, 1,11 or glutamate application. On a cellular level, electrophysiological changes are accompanied by significant shifts in intra-and extracellular ion concentrations, 12 cellular swelling, 13 dendritic beading, 14 and changes in gene expression.…”
Section: Introductionmentioning
confidence: 99%